Dynamic Context Processing - Ceyhun Aksoy (Dilbilim Araştırmaları Dergisi)
The idea that the context of an utterance may have dynamic properties is not new, as explicated in various works in quite different ways (please see Garnham 1987: 47; James 1890; McClelland & Rumelhart 1981). However, there still seem to exist problematic points in studying context under this assumption; below is an attempt to discuss some of these points briefly.